PENERAPAN PENGEDALIAN HAMA TERPADU MELALUI TANAMAN REFUGIA PADA TANAMAN PADI (Oryza sativa L.) - Kristiana, Lia (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
The use of natural enemies to control pests is a natural way that is safe for humans and the environment. One way this can be done is by conservation of natural enemies. Conservation is generally carried out through habitat management, namely by planting flowering plants that function as a source of feed, hosts (alternative prey, refuge) for natural enemies of pests. Refugia is a cultivated plant and has the potential to support natural enemy habitats ((both predators and parasites). The research method is experimental, namely comparing land that uses refugia plants and land that does not use refugia plants (conventional). This research was carried out on rice cultivation owned by farmers in Kangenan Village, Pademawu District, Pamekasan Regency. The study lasted for approximately 3 (three) months starting from April -June 2023. Data analysis using t-test by comparing the number of pests on land planted with reugia and conventional land.The results showed that the average number of locust pests on refugia land was 1.542857 and on conventional land 2.057143, the average number of walang sangit pests was 1.25714286 and conventional land was 2.05714286, the average number of caterpillar pests was 1.228571 and on conventional land was 1.885714.While the number of natural enemies of dragonflies on refugia land was 2.69 and on conventional land was 2.49. Based on the results of T tests on refugia and conventional land, locust pest Tstar 3.378975544 was obtained greater than Tcritical one1 1.782287548 , Tstar caterpillar pest 3.189526128 greater than Tcritical one 1.782287548, Tstar pest walang sangit 2.172198564 greater than Tcritical one 1.782287548 means that refugia plants can affect pests on rice plants because of the presence of refugia plants on the edge of the field as a temporary shelter for natural enemies.